The Role of Mating in Oviduct Biology - Cardenas-Sankan, G; Orihuela-Diaz, P; Reuquen-Lopez, P; Orostica, M (John Wiley and Sons Inc., 2016)
The oviduct connects the ovary to the uterus, and is subject to changes that influence gamete transport, fertilization, and early embryo development. The ovarian steroids estradiol and progesterone are largely responsible for regulating oviduct function, although mating signals also affect the female reproductive tract, both indirectly, through sensory stimulation, and directly, through contact with seminal plasma or spermatozoa. The resulting alterations in gene and protein expression help establish a microenvironment that is appropriate for sperm storage and selection, embryo development, and gamete transport. Mating may also induce the switch from a non-genomic to a genomic pathway of estradiol-accelerated oviduct egg transport, reflecting a novel example of the functional plasticity in well-differentiated cells. This review highlights the physiological relevance of various aspects of mating to oviduct biology and reproductive success. Expanding our knowledge of the mating-associated molecular and cellular events in oviduct cells would undoubtedly facilitate new therapeutic strategies to treat infertility attributable to oviduct pathologies. Mol. Reprod. Dev. 83: 875–883, 2016 © 2016 Wiley Periodicals, Inc. © 2016 Wiley Periodicals, Inc.